ЗАСТОСУВАННЯ НАДПРОВІДНИХ ІНДУКТИВНИХ НАКОПИЧУВАЧІВ (НПІН) ДЛЯ ДЕМПФУВАННЯ НЕРЕГУЛЯРНИХ КОЛИВАНЬ ПЕРЕТОКУ ПОТУЖНОСТІ - Васецький , Ю.М.; Мазуренко , І.Л.; Павлюк , А.В. (Інститут електродинаміки НАН України, Київ, 2012)
Possibility of use of SMES as dynamic active means for damping of low-frequency irregular power fluctuations in electric power system is shown. Regulation parameters are chosen, energy as well as mass and size parameters of new configuration SMES are defined. At the proposed regulation nay characteristic period of non compensated fluctuations corresponds to chosen time of smoothing and itfrequency is not dangerous to occutrence of emergency mode of operation. References 4, table 1, figures 2.